Increased Levels of NF-kB-Dependent Markers in Cancer-Associated Deep Venous Thrombosis. - Grazia Malaponte; Salvatore S Signorelli; Valentina Bevelacqua; Jerry Polesel; Martina Taborelli; Claudio Guarneri; Concettina Fenga; Kazou Umezawa; Massimo Libra (PLoS ONE, 2015)
Several studies highlight the role of inflammatory markers in thrombosis as well as in cancer. However, their combined role in cancer-associated deep vein thrombosis (DVT) and the molecular mechanisms, involved in its pathophysiology, needs further investigations. In the present study, C-reactive protein, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1β), matrix metalloproteases-9 (MMP-9), vascular endothelial growth factor (VEGF), tissue factor (TF), fibrinogen and soluble P-selectin, were analyzed in plasma and in monocyte samples from 385 cancer patients, of whom 64 were concomitantly affected by DVT (+). All these markers were higher in cancer patients DVT+ than in those DVT-. Accordingly, significantly higher NF-kB activity was observed in cancer patients DVT+ than DVT-. Significant correlation between data obtained in plasma and monocyte samples was observed. NF-kB inhibition was associated with decreased levels of all molecules in both cancer DVT+ and DVT-. To further demonstrate the involvement of NF-kB activation by the above mentioned molecules, we treated monocyte derived from healthy donors with a pool of sera from cancer patients with and without DVT. These set of experiments further suggest the significant role played by some molecules, regulated by NF-kB, and detected in cancer patients with DVT. Our data support the notion that NF-kB may be considered as a therapeutic target for cancer patients, especially those complicated by DVT. Treatment with NF-kB inhibitors may represent a possible strategy to prevent or reduce the risk of DVT in cancer patients.